Faces of America : How 12 Extraordinary People Discovered their Pasts. - Louis, Gates Henry (NYU Press, 2010)
As a nation of immigrants, the American experience is vibrantly defined by the diverse racial, ethnic, cultural, and religious heritage of its people. Perhaps because so many of their ancestors migrated to this country relatively recently, Americans are especially concerned with their family trees, carving out personal histories by combing through documents such as wills and estate records, federal and state censuses, and private family papers, and mining the stories and tales handed down to them by their forebears. Since 2007, the Harvard scholar Henry Louis Gates, Jr., has been helping Afric.